Short Periodic VLF Emissions Observed Simultaneously by Van Allen Probes and on the Ground. Issue 20 (21st October 2021) - Demekhov, A. G.; Titova, E. E.; Manninen, J.; Nikitenko, A. S.; Pilgaev, S. V.
Abstract: We present simultaneous observations of very low‐frequency emissions with periodic bursts by Van Allen Probe near geomagnetic equator and Kannuslehto and Lovozero ground‐based sites. The repetition period and ground–spacecraft delay are consistent with guided whistler wave propagation between conjugate ionospheres. In contrast to lightning whistlers, the group velocity dispersion is not accumulated from one burst to another, thus implying a nonlinear mechanism of its compensation. Two regimes are observed. In one regime, Poynting flux direction alternates in the magnetosphere, and the burst period (2 s) is half of that detected on the ground (4 s), corresponding to single‐wave packet bouncing along the field line. This regime is switched to the other one, with burst period unchanged in the magnetosphere but halved on the ground. In this second regime, no alternating Poynting flux direction is observed. The second regime corresponds to two symmetrically propagating wave packets synchronously meeting at the equator. Plain Language Summary: The near‐Earth space is populated by energetic charged particles (ions and electrons) forming radiation belts and ring current and having energies from several keV to several MeV. Energetic particles can damage spacecraft electronics and affect the health of humans in space. Recently, the radiation belt dynamics attracted great interest among researchers and new spacecraft research missions have been launched for these studies. Dynamics of radiation belt electrons is to a great extent determined by energetic particle interaction with very low‐frequency (VLF) electromagnetic waves (∼ 1 0 3 – 10 4  Hz). These waves can propagate from one hemisphere to the other along geomagnetic field lines, and characteristic propagation times are 1–5 s depending on the latitude and plasma density. We study a distinct type of VLF emissions whose amplitude is periodically modulated with periods of several seconds (periodic emissions). In contrast to previous studies using ground‐based data, we use simultaneous observations by Van Allen Probe in the equatorial magnetosphere and ground stations. Our analysis allowed us to show for the first time that the modulation period of these emissions is related to the wave propagation time between conjugate hemispheres. We observed two regimes corresponding to a single‐wave packet or two symmetrically propagating wave packets. Key Points: Van Allen Probes and ground‐based sites observed correlated periodic very low‐frequency emissions with periods of 2 or 4 s consistent with wave bouncing Poynting flux directions at Van Allen Probes were opposite in neighboring pulses in one regime and parallel in the other regime The pulse period onboard the spacecraft was half of that on the ground in the first regime and the periods were equal in the second regime